COVID-19 vaccine effectiveness among healthcare workers: a hospital-based cohort study - Gaio, Vânia (2023)
Objectives: Healthcare workers (HCWs) were the first to be prioritised for COVID-19 vaccination. This study aims to estimate the COVID-19 vaccine effectiveness (VE) against SARS-CoV-2 symptomatic infection among HCWs in Portuguese hospitals. Design: Prospective cohort study. Setting and participants: We analysed data from HCWs (all professional categories) from three central hospitals: one in the Lisbon and Tagus Valley region and two in the central region of mainland Portugal, between December 2020 and March 2022. VE against symptomatic SARS-CoV-2 infection was estimated as one minus the confounder adjusted HRs by Cox models considering age group, sex, self-reported chronic disease and occupational exposure to patients diagnosed with COVID-19 as adjustment variables. Results: During the 15 months of follow-up, the 3034 HCWs contributed a total of 3054 person-years at risk, and 581 SARS-CoV-2 events occurred. Most participants were already vaccinated with a booster dose (n=2653, 87%), some are vaccinated with only the primary scheme (n=369, 12.6%) and a few remained unvaccinated (n=12, 0.4%) at the end of the study period. VE against symptomatic infection was 63.6% (95% CI 22.6% to 82.9%) for HCWs vaccinated with two doses and 55.9% (95% CI -1.3% to 80.8%) for HCWs vaccinated with one booster dose. Point estimate VE was higher for individuals with two doses taken between 14 days and 98 days (VE=71.9%; 95% CI 32.3% to 88.3%). Conclusion: This cohort study found a high COVID-19 VE against symptomatic SARS-CoV-2 infection in Portuguese HCWs after vaccination with one booster dose, even after Omicron variant occurrence. The small sample size, the high vaccine coverage, the very low number of unvaccinated individuals and the few events observed during the study period contributed to the low precision of the estimates.